Older adults with advanced cancer are selective in sharing and seeking information with social networks. Issue 10 (October 2022) - Kehoe, Lee; Sanapala, Chandrika; DiGiovanni, Grace; Yousefi-Nooraie, Reza; Yilmaz, Sule; Bauer, Jessica; Loh, Kah Poh; Norton, Sally; Duberstein, Paul; Kamen, Charles; Gilmore, Nikesha; Gudina, Abdi; et al.
Abstract: Background: Little is known about how older adults (OA) with advanced cancer interact with social network members (NM), and the nature of communication. This qualitative study aimed to characterize the processes by which OAs with cancer engage with NMs regarding their illness. Methods: OAs 65 + with advanced cancer and considering treatment (n = 29) and NMs (n = 18) underwent semi-structured interviews asking 1) about their illness understanding; 2) to identify NMs with whom OAs discuss health-related matters; and 3) to describe the content, process, and impact of those illness-related conversations. Three coders analyzed transcribed interviews. Codes were categorized and emergent themes were identified to generate hypotheses. Results: OAs seek NMs with medical backgrounds for cancer-related information and NMs with personal experience of a serious illness for emotional support. Patients characterize geographical location, frequency of communication, and length of NM relationship as factors that influence the nature of support the NM provides. Additionally, differences emerged between OA and NM perspectives on the depth of conversations and decision-making. Conclusions: A better characterization of how OAs' seek and share information and support may improve medical communication, disease understanding, and support goals-concordant care. Highlights: Older patients are selective in seeking and sharing information with network members. Geographical distance, length of relationship, and frequency of communication influence the selective sharing process. Network members with medical background are sought out for cancer related advice. Patients characterize conversations about cancer as surface-level, while network members describe more in-depth conversations. Patients describe decisions as shared, while network members reported the patients made their own decisions.